2007
DOI: 10.1152/ajpendo.00341.2007
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of clock genes in the suprachiasmatic nucleus blocks prolactin surges and alters FRA expression in the locus coeruleus of female rats

Abstract: Poletini MO, McKee DT, Kennett JE, Doster J, Freeman ME. Knockdown of clock genes in the suprachiasmatic nucleus blocks prolactin surges and alters FRA expression in the locus coeruleus of female rats. Am J Physiol Endocrinol Metab 293: E1325-E1334, 2007. First published August 28, 2007; doi:10.1152/ajpendo.00341.2007.-The nature of the circadian signal from the suprachiasmatic nucleus (SCN) required for prolactin (PRL) surges is unknown. Because the SCN neuronal circadian rhythm is determined by a feedback lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 77 publications
3
25
0
Order By: Relevance
“…In the present study, an AS-ODN injection that decreased the expression of per1 , per2, and clock [14] within neurons of the SCN abolished both PRL surges in cervically stimulated OVX rats. We have previously demonstrated this same effect on the PRL secretory surge induced by estradiol in OVX and proestrus rats [13]. Taken together, these data link PRL secretion observed in different stages of the reproductive cycle to the molecular clock mechanism in the SCN.…”
Section: Discussionsupporting
confidence: 68%
See 4 more Smart Citations
“…In the present study, an AS-ODN injection that decreased the expression of per1 , per2, and clock [14] within neurons of the SCN abolished both PRL surges in cervically stimulated OVX rats. We have previously demonstrated this same effect on the PRL secretory surge induced by estradiol in OVX and proestrus rats [13]. Taken together, these data link PRL secretion observed in different stages of the reproductive cycle to the molecular clock mechanism in the SCN.…”
Section: Discussionsupporting
confidence: 68%
“…Control animals were injected with RS-ODNs, which had the same nucleotide content (% AGCT) as the AS-ODN but were not complementary to clock gene mRNA sequences. As demonstrated previously in our laboratory, this treatment leads to a knockdown of PER1, PER2, and CLOCK expression in the SCN by more than 60% within 6 h of injection and to a decrease in the number of CLOCK-positive neurons in the SCN at 08.00 and 16.00 h [13,14]. We have also previously reported that this treatment disrupts the circadian drinking behavior of OVX rats [14].…”
Section: Methodssupporting
confidence: 68%
See 3 more Smart Citations